The use of prequestion method to improve students reading comprehension - Syamsia, Syamsia; Umaternate, Nafisa (Universitas Negeri Medan, 2025)
The aim of this research was to know about how the students’ reading comprehension can be improve by using pre questioning method at the second grade students of SMP Negeri 1 Mangoli. In fact, based on the result of pre observation, the students of SMP Negeri 1 Mangoli have some problems in reading. They got lacks in vocabulary mastery, missed understanding, and they still translate word by word. The setting of this research was SMP Negeri 1 Mangoli. It consist six classes, each classes consist of 22 students. So the total number of population are 138 students. The subject of this research were the second grade students of SMP Negeri 1 Mangoli, they were 22 students. this research used classroom action research. Based on the result of the implementation of pre questioning technique to improve students’ reading comprehension in the second grade students at SMP Negeri 1 Mangoli, the researcher concluded that the use of pre questioning technique can improve the students’ reading comprehension. The students’ result in cycle I, it was showed that just 5 students reach the result were success or in other word just 5 of 22 students pass the passing grade (70). While there were 17 of 22 students got the score under the passing grade. While, the students’ result in cycle II, there were 20 of 22 students reached the result were success or in other word 20 students pass the passing grade (70). While just two students got the score under the passing grade.